2020
DOI: 10.2478/raon-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional MRI evaluation of the effect of bladder volume on prostate translocation and distortion

Abstract: BackgroundThe accuracy of any radiation therapy delivery is limited by target organ translocation and distortion. Bladder filling is one of the recognised factors affecting prostate translocation and distortion. The purpose of our study was to evaluate the effect of bladder volume on prostate translocation and distortion by using detailed three-dimensional prostate delineation on MRI.Patients and methodsFifteen healthy male volunteers were recruited in this prospective, institutional review board-approved stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…17 There are several studies which have investigated the influence of consistent bladder filling between RT planning and treatment on the inter-fraction prostate position. [17][18][19] It is suggested that a more than twofold difference in bladder volume between RT planning and treatment could cause moderate prostate translocations and distortions especially in the anterior/posterior direction and between the prostatic base and the apex. 19 This may result in a higher chance of geometrical miss leading to poorer tumour control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 There are several studies which have investigated the influence of consistent bladder filling between RT planning and treatment on the inter-fraction prostate position. [17][18][19] It is suggested that a more than twofold difference in bladder volume between RT planning and treatment could cause moderate prostate translocations and distortions especially in the anterior/posterior direction and between the prostatic base and the apex. 19 This may result in a higher chance of geometrical miss leading to poorer tumour control.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] It is suggested that a more than twofold difference in bladder volume between RT planning and treatment could cause moderate prostate translocations and distortions especially in the anterior/posterior direction and between the prostatic base and the apex. 19 This may result in a higher chance of geometrical miss leading to poorer tumour control. The use of daily IGRT in this study will have ensured accurate RT delivery to both bladder filling groups which is supported by the similar population systematic and random errors.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Motion artefact is an important issue for MR imaging, although the low pelvic position of the prostate limits the effects of respiratory motion and small bowel peristalsis, the longer acquisition of T2-FRFSE sequences makes them prone to artefact from bulk patient movement or rectal wall and/or bladder spasm. 17-20 Motion artefact due to rectal spasm is typically visualised as “jumping” between slices, due to the time delay in acquisition of interleaved slices, and the different position of prostate if the rectal wall has moved within the time-interval. 21 Rectal preparation with a micro-enema has shown only questionable benefit in reducing such motion, 22-24 however, rectal spasm can be reduced by administration of antispasmodics, provided these are routinely available and not clinically contraindicated.…”
Section: Discussionmentioning
confidence: 99%
“…First, PSAD may be subject to errors in the measurement of prostate size, as most radiologists estimate prostate volume with formula-based means. 18 19 20 Second, as PSAD is inherently a small number, stratification into groups would rely on differences at two or more decimal places, increasing the likelihood of errors. If a PSAD of 0.15 ng ml −2 was employed as a single cutoff 21 22 in PI-RADS score 3 lesion patients, there would be more heterogeneity than using the four PHI categories in this study.…”
Section: Discussionmentioning
confidence: 99%